PERAN PEMBERIAN INSENTIF DALAM MODERASI PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP LOYALITAS KARYAWAN PADA PT. BANK SUMUT CABANG SUKARAMAI MEDAN - Aliza Azzahra; T. Lyza Tahura Chairunnisa; Rizki Putra (Jurnal Ilmu Manajemen METHONOMIX, 2021)
This study aims to determine the effect of job characteristics on employee loyalty of PT. Bank SUMUT, Sukaramai Medan branch, partially to find out whether incentive support moderates the effect of job characteristics on employee loyalty at PT. Bank SUMUT, Sukaramai Medan Branch. The population in this study amounted to 156 people and using the Slovin formula obtained a sample of 112people. Measurement of variables using a Likert scale from strongly agree (score 4) to strongly disagree (score 1). The data were analyzed by using statistical techniques such as validity test, reliability test, simple linear regression, Moderating Regression Analysis (MRA), classical assumption test, model test (F test), partial test (t-test), and test coefficient of determination (R2). The results of this study showed that job characteristics have a positive and significant effect on employee loyalty of PT. Bank SUMUT, Sukaramai Medan Branch. Incentives have no effect on employee loyalty of PT. Bank SUMUT, Sukaramai Medan Branch. Providing incentives is not proven to moderate job characteristics towards employee loyalty at PT. Bank SUMUT, Sukaramai Medan Branch.